Finite element modelling and analysis of C7-T2 - Tang, Alicia (2018)
Finite element methods have been recognised to be a much suitable way for carrying out dimensional and stress analysis, rather than In vivo methods, which are invasive and expensive. Being non-experimental meant that spinal injuries can be avoided, given the more extensive information on spinal behaviour and injury mechanisms. This report covers the constructed finite element models (FEM) for cervical vertebra section 7 (C7) and thoracic vertebrae sections 1 (T1) and 2 (T2), of a given patient. With the aid of ANSYS 16.2, area and volume creation of C7, T1 and T2 were done using the key points and lines from the IGES files. After which, meshing of the structures were generated. The results were then validated against past research papers by adhering to the material properties, boundary conditions and applied force. This report determines the difference in Rotation of Motion between C7-T2 due to translation zone and the angulations of facets being different for smooth transition of C7-T1.